Calculation of the Coupling Coefficient in Step-Index Multimode Polymer Optical Fibers Based on the Far-Field Measurements - Savović, Svetislav; Djordjevich, Alexandar; Drljača, Branko; Simović, Ana; Min, Rui (Frontiers in Physics, 2022)
Using the power flow equation (PFE), this article investigates mode coupling in multimode (MM) step-index (SI) polymer optical fiber (POF). This equation's coupling coefficient was initially fine-tuned so that it could appropriately reconstruct previously recorded far-field (FF) power distributions. The equilibrium mode distribution (EMD) and steady-state distribution (SSD) in the SI POF were found to be obtained at lengths of 15 and 41 meters, respectively. These lengths are substantially shorter than their glass optical fiber counterparts. Such characterization of the investigated POF can be used in its employment as a part of the communication or sensory system.